Assessment of murine lung mechanics outcome measures: alignment with those made in asthmatics - Walker, Julia K.; Kraft, Monica; Fisher, John T. (Frontiers in Physiology, 2013)
Although asthma is characterized as an inflammatory disease, recent reports highlight the importance of pulmonary physiology outcome measures to the clinical assessment of asthma control and risk of asthma exacerbation. Murine models of allergic inflammatory airway disease have been widely used to gain mechanistic insight into the pathogenesis of asthma; however, several aspects of murine models could benefit from improvement. This review focuses on aligning lung mechanics measures made in mice with those made in humans, with an eye toward improving the translational utility of these measures. A brief description of techniques available to measure murine lung mechanics is provided along with a methodological consideration of their utilization. How murine lung mechanics outcome measures relate to pulmonary physiology measures conducted in humans is discussed and we recommend that, like human studies, outcome measures be standardized for murine models of asthma.